Building Student Entrepreneurship Through The Kkm-Iptek Program For Entrepreneurs At Serang Raya University - Hamdan Hamdan (Jurnal Pengabdian Masyarakat Akademisi, 2022)
The Aim of The activities of the Serang Raya University Business Incubator include: developing an entrepreneurial spirit, training management and business skills for tenants, business consulting, reviewing established companies and facilitating tenants in entrepreneurship to produce new entrepreneurs. TheÂ Students who have started entrepreneurship, students of the Entrepreneurship Student Creativity Program (PKMK) or other Student Creativity Programs (PKM), graduating students who are interested or just starting a business can perfect the entrepreneurial activities that have been carried out previously, to increase their business. The service unit for the Business Incubator program at the University of Serang Raya in 2022 provides entrepreneurship motivation to 40 students, all of whom are other PKMK/PKM students, students who are starting new businesses and students who have graduated, then from that number 17 were selected to become tenants of prospective entrepreneurs. At the end of the program, 6 students and graduate students have succeeded in becoming new entrepreneurs with various business fields, including: wood crafts, rope bags, headscarves, patchwork, campus canteen culinary businesses and vegetable donuts as well as a bicycle rental service business. motorcycle.